Sleep Quality as a Determinant of Memory Function in Medical Students at Universitas Muslim Indonesia - Andi Inas Farhamila Armin; Fendy Dwimartyono; Achmad Harun Muchsin; Muh Alim Jaya; Nevi Sulvita Karta (Faculty of Medicine, Universitas Tadulako, 2026)
Background: Poor sleep quality is a common issue among medical students and may negatively affect cognitive functions, particularly memory, which plays a crucial role in learning. Objective: This study aimed to analyze the influence of sleep quality on memory function among medical students at the Faculty of Medicine, Universitas Muslim Indonesia, from the 2022, 2023, and 2024 cohorts. Methods: A cross-sectional design was applied to 91 students selected using proportional stratified random sampling. Sleep quality was assessed with the Pittsburgh Sleep Quality Index (PSQI), while memory performance was measured using the Everyday Memory Questionnaire (EMQ). Data were analyzed using Two-Way ANOVA. Results: Sleep quality significantly affected memory function (p = 0.000), with students reporting poor sleep showing higher memory impairment. Cohort level also had a significant effect (p = 0.000), where senior students demonstrated the highest prevalence of poor sleep quality (75%) and memory impairment (94.4%). Moreover, a significant interaction between sleep quality and cohort level (p = 0.018) indicated that the impact of sleep quality on memory varied across academic years. Conclusion: These findings highlight the importance of implementing interventions such as sleep management education, stress regulation, and regular monitoring of sleep quality, particularly for senior students.